Fremd bin ich eingezogen, Fremd zieh’ ich wieder aus: the common yet not shared crises of opera singers (Colloquia Comparativa Litterarum, 2025)
There is almost no empirical research into the later stages of classical singers’ careers and the difficulties faced. A quantitative study of operatic soloists was conducted via online questionnaire to ascertain when and how these difficulties manifest themselves. The survey divided the singers into 2 groups: those who stopped their solo careers as a result of the difficulties and those whose careers continued, in order to explore the differences between the responses of the 2 groups to the career downturn. This article posits that the singer’s crisis is a common experience, though one which singers seldom discuss amongst themselves. To illustrate this, it focuses on the 2 causes for career difficulties most often cited by the respondents: mental health issues and technical vocal problems. The study demonstrates a reluctance by singers to deal with anxiety, stress and self-doubt, even at the cost of their careers.